2022
DOI: 10.1186/s12888-022-04137-1
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological coherence, inclusive leadership and implicit absenteeism in obstetrics and gynecology nurses: a multi-site survey

Abstract: Background Implicit absenteeism is very common among clinical nurses. We aimed to evaluate the role of psychological coherence in the inclusive leadership and implicit absenteeism among obstetrics and gynecology nurses, to provide evidence to the clinical management of nurses. Methods Through the convenience sampling method, a survey of gynecology nurses in tertiary hospitals in 16 cities of Anhui Province, China was conducted using the General Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…Second, inclusive leadership, perceived organizational support, and presenteeism were all negatively correlated, i.e., the higher the nurses' perceived level of inclusive leadership, the lower their presenteeism, consistent with the research by Jin Y et al [ 20 ]. Leadership styles impact clinical nurses, patient experience, work quality, and work environment [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…Second, inclusive leadership, perceived organizational support, and presenteeism were all negatively correlated, i.e., the higher the nurses' perceived level of inclusive leadership, the lower their presenteeism, consistent with the research by Jin Y et al [ 20 ]. Leadership styles impact clinical nurses, patient experience, work quality, and work environment [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…High workload and ethically challenging duties are major problems for obstetric nurses (Holmlund et al, 2022). Feelings of powerlessness, work pressure, and work frustration among obstetrics and gynecology nurses are common in the work environment (Jin et al, 2022). Investigations have shown that obstetric nurses have psychological problems such as fear and hypochondria under the COVID-19 epidemic (Wu et al, 2021).…”
Section: Departmentmentioning
confidence: 99%
“…Implicit absenteeism refers to a state where employees may be physically present at work but are emotionally or mentally disengaged, resulting in decreased job performance and overall contribution to the workplace [ 19 ]. While this term may not be widely used in the literature, the concept aligns with the broader understanding of presenteeism, which involves employees being on the job but not fully engaged or productive [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may manifest as reduced productivity, lack of focus, and an overall decline in job performance [ 22 ]. Implicit absenteeism can also impact nurses’ performance in the workplace, such as reduced patient interaction, reduced awareness of occupational protection, and lack of participation in professional development [ 23 25 ]. Research has suggested a negative relationship between nurse burnout, a concept closely related to implicit absenteeism, and job performance.…”
Section: Introductionmentioning
confidence: 99%